Factors Predicting Anxiety and Depression Among Newly Diagnosed Breast Cancer Patients - วัฒนานุกิจ ภิญญดา; ศรีมรกต ผ่องศรี; พงศ์ถาวรกมล คนึงนิจ; จุฑาภิสิทธิ์ สืบวงศ์ (Journal of The Royal Thai Army Nurses, 2019)
This descriptive research design aimed to study the factors predicting anxiety and depression among newly diagnosed breast cancer patients. The sample group consisted of 107 patients aged 18 years and older, who were undergoing chemotherapy at outpatient department and breast cancer surgery at Siriraj Hospital. The data were collected using the demographic data form, Connor-Davidson Resilience Scale, Self-Blame Attributions, The State-Trait Anxiety Inventory (STAI) Form Y-I and Form Y-II, Hospital Anxiety and Depression Scale. Descriptive statistics, Pearson’s Product Moment Correlation, and Stepwise Multiple Regression Analysis were used in data analysis. The results of the study showed that the mean anxiety score was 2.82 (S.D. = 0.55) and the mean depression score was 0.98 (S.D. = 0.53). Resilience and trait anxiety could predict anxiety accounting for 72% of the variance (R2 = .720, p < .001). Self blame and trait anxiety could predict depression accounting for 59% of the variance (R2 = .590, p < .003). The findings yielded by the present study should be developed into screening assessment and care guidelines for breast cancer patients in terms of mental state during the newly diagnosed stage.